Charles Spence. - Spence, C (2014)
Working at the Crossmodal Research Laboratory in Oxford, Charles Spence tries to apply the latest insights from our growing neuroscience understanding of the rules governing multisensory integration to the design of better products, packages, places, interfaces, and foods, an area that can perhaps best be captured under the title of neuroscience-inspired multisensory design.